Talin at myotendinous junctions (The Rockefeller University Press, 1986)
Junctions formed by skeletal muscles where they adhere to tendons, called myotendinous junctions, are sites of tight adhesion and where forces generated by the cell are placed on the substratum. In this regard, myotendinous junctions and focal contacts of fibroblasts in vitro are analogues. Talin is a protein located at focal contacts that may be involved in force transmission from actin filaments to the plasma membrane. This study investigates whether talin is also found at myotendinous junctions. Protein separations on SDS polyacrylamide gels and immunolabeling procedures show that talin is present in skeletal muscle. Immunofluorescence microscopy using anti-talin indicates that talin is found concentrated at myotendinous junctions and in lesser amounts in periodic bands over nonjunctional regions. Electron microscopic immunolabeling shows talin is a component of the digitlike processes of muscle cells that extend into tendons at myotendinous junctions. These findings indicate that there may be similarities in the molecular composition of focal contacts and myotendinous junctions in addition to functional analogies.